2009
DOI: 10.1186/ar2816
|View full text |Cite
|
Sign up to set email alerts
|

Urinary TWEAK as a biomarker of lupus nephritis: a multicenter cohort study

Abstract: IntroductionTNF-like weak inducer of apoptosis (TWEAK) has been implicated as a mediator of chronic inflammatory processes via prolonged activation of the NF-κB pathway in several tissues, including the kidney. Evidence for the importance of TWEAK in the pathogenesis of lupus nephritis (LN) has been recently introduced. Thus, TWEAK levels may serve as an indication of LN presence and activity.MethodsMulticenter cohorts of systemic lupus erythematosus (SLE) patients and controls were recruited for cross-section… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
137
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 159 publications
(146 citation statements)
references
References 31 publications
7
137
0
2
Order By: Relevance
“…20,21 In a cross-sectional single-cohort study using a modest sampling of patients with LN, we previously reported that serum or urine CSF-1 was elevated in patients with LN compared with those who had other noninflammatory kidney diseases and healthy controls; in that study we also found that amplified CSF-1 levels correlated with more severe clinical disease activity. 8 Another study indicated that flares were more likely in patients with persistently increased regulated upon activation normal T cell expressed and presumably secreted or M-CSF (also known as CSF-1) levels in urine after induction therapy using group survival curve analysis.…”
Section: Discussionmentioning
confidence: 59%
“…20,21 In a cross-sectional single-cohort study using a modest sampling of patients with LN, we previously reported that serum or urine CSF-1 was elevated in patients with LN compared with those who had other noninflammatory kidney diseases and healthy controls; in that study we also found that amplified CSF-1 levels correlated with more severe clinical disease activity. 8 Another study indicated that flares were more likely in patients with persistently increased regulated upon activation normal T cell expressed and presumably secreted or M-CSF (also known as CSF-1) levels in urine after induction therapy using group survival curve analysis.…”
Section: Discussionmentioning
confidence: 59%
“…In addition, a variety of studies have demonstrated the value of TWEAK in assessing renal damage severity (10)(11)(12). Notably, it has been reported that urine TWEAK content in patients with active LN was significantly higher than in those with inactive LN (13), and that urine TWEAK level was correlated with the degree of renal damage (14). Previous results also indicated that TWEAK was highly expressed in the renal tissue of an LN animal model (15).…”
Section: Introductionmentioning
confidence: 97%
“…16 In clinical studies, significantly higher urinary TWEAK levels were present in human LN, which increased with renal flares. [17][18][19][20] Interestingly, intrarenal TWEAK and Fn14 expression varied with the histologic class of LN and correlated with the activity index. 21,22 Finally, elevated production of TWEAK in lupus PBMCs correlated with disease activity and proteinuria.…”
mentioning
confidence: 95%